Circulating innate lymphoid cells and IL-18 as potential immune biomarkers in thymic tumors - Maresca, Daniela Claudia; Saponaro, Maria Rosaria; La Civita, Evelina; Tortora, Marianna; Romano, Benedetta; Pietroluongo, Erica; Somma, Fabio; Giuliano, Mario; Servetto, Alberto; Palmieri, Giovannella; Ianaro, Angela; Terracciano, Daniela; et al. (Frontiers in Immunology, 2025)
IntroductionThymic epithelial tumors (TETs) are rare malignancies frequently associated with autoimmunity. However, circulating immune biomarkers for patient stratification and disease monitoring remain undefined. Innate lymphoid cells (ILCs) are emerging regulators of tumor immunity, but their role in TETs has not yet been characterized.MethodsPeripheral blood samples from 32 patients with histologically confirmed TETs and 20 healthy donors were analyzed by multiparametric flow cytometry to quantify circulating ILC subsets. Serum cytokine concentrations were measured using multiplex immunoassays. Patients were stratified according to histology, disease activity, and presence of autoimmune manifestations.ResultsTETs displayed a significant expansion of circulating ILCs, mainly driven by an enrichment of ILC1, which was more pronounced in patients with active disease and in those with thymic carcinoma. Serum IL-18 levels were elevated—particularly in thymic carcinoma—and correlated with higher concentrations of type 2 cytokines (IL-4, IL-5, IL-9, IL-13). No concomitant increase in canonical ILC1 effector cytokines, including IFN-γ, was observed, indicating a functional dissociation between ILC1 expansion and their expected cytokine profile.DiscussionThese findings delineate a distinct systemic immune signature in TETs, characterized by IL-18 upregulation and altered ILC1 dynamics, with potential implications for immune regulation and autoimmunity. Circulating ILC profiling combined with IL-18 measurement may represent a promising approach for patient stratification, disease monitoring, and the development of novel immunomodulatory strategies in TETs.